ROLE OF PHYSICAL ACTIVITY IN THE PREVENTION AND MANAGEMENT OF NON-ALCOHOLIC FATTY LIVER DISEASE - SHAH, MA; KHAN, AA; NOOR, .; AHMAD, S (Biological and Clinical Sciences Research Journal, 2023)
Non-alcoholic Hepatic Steatosis (NAFLD) is a major global cause of chronic liver disease. Its prevalence increases with the rise in metabolic syndrome components, primarily obesity and insulin resistance. The etiology of NAFLD is multifactorial, and recent studies suggest a "multiple hit" hypothesis that includes a combination of genetic, metabolic, and environmental factors. Lifestyle habits, including physical activity, play a significant role in its management. This study investigated the relationship between physical activity levels and the prevalence and severity of NAFLD in adults. A cross-sectional approach was used with a total of 250 participants. The participants were evenly divided into two groups: those diagnosed with NAFLD (n=125) and control subjects without NAFLD (n=125). Stratification was carefully executed to ensure equivalence in age, gender, and main co-morbidities to eliminate potential confounding variables. Among the 250 participants, with 125 individuals each in the NAFLD and control groups, no significant differences in age, BMI, or prevalence of co-morbidities such as diabetes and hypertension were observed. However, hepatic biochemical markers exhibited substantial differences between groups. ALT levels averaged 67.3 23.7 U/L for NAFLD participants compared to 24.2 ± 10.8 U/L in controls (p < 0.001); AST levels were at 54.8 ± 19.6 U/L for NAFLD versus 23.4 ± 8.9 U/L for controls (p < 0.001); GGT showed 89.2 ± 32.5 U/L in NAFLD individuals contrasting with 29.5 ± 13.4 U/L in controls (p < 0.001). Furthermore, the FIB-4 index was higher in the NAFLD cohort (2.4 ± 0.6) than in controls (1.3 ± 0.4; p < 0.001), and serum Albumin levels in NAFLD participants were 3.8 ± 0.5 g/dL, notably lower than the control’s 4.5 ± 0.3 g/dL (p < 0.001). The study concludes that physical activity is inversely associated with the prevalence and severity of NAFLD. Regular physical activity may be a key strategy in preventing and managing NAFLD.